Cannabinoid type 1 receptors in astrocytes - Marsicano, Giovanni (Henry Stewart Talks, 2014)
Mechanism of action of cannabinoid type 1 receptors (CB1), Endocannabinoids (ECBs) and their role as retrograde neurotransmitters, The Cre/loxP system, CB1 in neurons and in astrocytes, CB1 deletion in specific neuronal populations, Cannabinoids and working memory via LTD in vivo (NMDAR, AMPAR, neuronal CB1R, astroglial CB1R), Testing working memory (Delayed non-matching to sample T-maze test & Delayed matching to place in Morris water maze)